The Effect of Perceived Ease, Risk and Financial Literacy on the Use of QRIS as a Digital Payment in MSMEs - Ida Riskawati; Mardhiyaturrositaningsih; Saekhu (Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Purpose - This study aims to examine the Influence of Perceived Ease, Perceived Risk and Financial Literacy on the Decision to Use the Quick Response Code Indonesian Standard (QRIS) as a Digital Payment in MSMEs. Method - This research is a quantitative research type with a sample of 100 MSMEs. This study uses multiple regression analysis to identify the Influence of Perceived Ease, Perception of Risk and Financial Literacy on the Decision to Use the Quick Response Code Indonesian Standard (QRIS) as Digital Payment in MSMEs. Result - The results of this study indicate that there is an influence between Perceived Ease, Perception of Risk and Financial Literacy on the Decision to Use QRIS. Implication - This study identifies the use of QRIS in MSMEs in Semarang. Originality - This paper identifies that there are factors of Perceived Ease, Perception of Risk and Financial Literacy as factors causing the decision of MSMEs in Semarang City to use QRIS digital payments. Keywords: Financial Literacy, Perceived Ease, QRIS, Risk